Central-Local Administrative and Governance Relationships in Two Ukrainian Cities: Kyiv and Odessa - Natalya KOLISNICHENKO; Allan ROSENBAUM (Transylvanian Review of Administrative Sciences, 2006)
The institution of local self-government occupies an increasingly important position in Ukrainian society. However, the contemporary system of local self-government in Ukraine is still not consistent with the principles of the European Charter of Local Self-government. In areas such as access to sources of revenue, policy initiation and citizen involvement in local governance, municipal governments in Ukraine frequently fall significantly short of expected European standards. In part, this is due to the lingering influence of the Soviet totalitarian past on the mentality of both the Ukrainian legislators and the representatives of local governments who are working to create democratic principles of true people’s power. Too often, the creation of independent self-governance authority conflicts with the strong desire of some political forces to transform local self-government into an appendage of state (national government) power under rigid and comprehensive control. But, in spite of this, democratic principles are finding their way into the re-thinking of the role of local self-government in Ukranian society.